Generalised multiparty session types with crash-stop failures - Barwell, AD; Scalas, A; Yoshida, N; Zhou, F (Schloss Dagstuhl – Leibniz-Zentrum für Informatik, 2022)
Session types enable the specification and verification of communicating systems. However, their theory often assumes that processes never fail. To address this limitation, we present a generalised multiparty session type (MPST) theory with crash-stop failures, where processes can crash arbitrarily. Our new theory validates more protocols and processes w.r.t. previous work. We apply minimal syntactic changes to standard session π-calculus and types: we model crashes and their handling semantically, with a generalised MPST typing system parametric on a behavioural safety property. We cover the spectrum between fully reliable and fully unreliable sessions, via optional reliability assumptions, and prove type safety and protocol conformance in the presence of crash-stop failures. Introducing crash-stop failures has non-trivial consequences: writing correct processes that handle all crash scenarios can be difficult. Yet, our generalised MPST theory allows us to tame this complexity, via model checking, to validate whether a multiparty session satisfies desired behavioural properties, e.g. deadlock-freedom or liveness, even in presence of crashes. We implement our approach using the mCRL2 model checker, and evaluate it with examples extended from the literature.